IDEAS FOR STRENGTHENING SUPREME COURT JUDICIAL REVIEW AUTHORITY IN REVIEW OF REGIONAL REGULATIONS - Risnain, Muh (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2020)
AbstractThe problem of judicial review of regional regulations in the Supreme Court is a serious academic and practical issue that needs to be resolved after the issuance of the decision of the Constitutional Court Number 137 / PUU-XIII / 2015. There are two problems in this paper, first, the legal implications of the Constitutional Court Decision Number 137 / PUU-XIII / 2015 on institutional and legal procedures for judicial review of regional regulations in the Supreme Court, secondly, how is the concept of the Supreme Court judicial review carried out through renewal of procedural law Trial Judicial Review in the Supreme Court? Based on the discussion above, we can conclude two things, first, the legal implications of the Constitutional Court Decision Number 137 / PUU-XIII / 2015 on the institutional and legal procedures for judicial review of regional regulations in the Supreme Court are the stronger and increasing authority of judicial review in Supreme Court. This decision ended the dualism of review of local regulations from judicial review by the Supreme Court and executive review of regional regulations by the Ministry of Home Affairs to only a judicial review by the Supreme Court, also potentially increasing the number of cases of judicial review in the Supreme Court. Second, the concept of the implementation of a judicial review by the Supreme Court is carried out through legal renewal of the judicial review proceedings in the Supreme Court by including several important substances, related to hearings that are open to the public, the existence of a preliminary examination, hearing, verdict and decision making that are more open and fair.Keywords: Regional Regulation, Judicial Review, and ReformationÂ ABSTRAKProblem judicial review Perda di Mahkamah Agung menjadi persoalan akademik dan praktikal serius yang perlu dipecahkan pascakeluarnya putusan Mahkamah konstitusi Nomor 137/PUU-XIII/2015. Terdapat dua masalah dalam tulisan ini, pertama, implikasi hukum Putusan Mahkamah konstitusi Nomor 137/PUU-XIII/2015 terhadap kelembagaan dan hukum acara judicial review perda di mahkamah agung, kedua, bagaimanakah konsep pelaksanaan judicial review perda oleh mahkamah agung dilakukan melalui pembaharuan hukum acara persidangan judicial review di mahkamah agung?. Berdasarkan pembahasan di atas maka dapat disimpulkan dua hal , pertama, implikasi hukum Putusan Mahkamah konstitusi Nomor 137/PUU-XIII/2015 terhadap kelembagaan dan hukum acara judicial review perda di mahkamah agung adalah semakin kuat dan meningkatnya kewenangan judicial review di mahakamah agung. Putusan ini mengakhiri dualisme review perda dari judicial review oleh MA dan executive review perda oleh kemendagri menjadi hanya judicial review oleh Mahkamah Agung, juga berpotensi meningkatkan jumlah perkara judicial review perda di mahkamah agung. Kedua, konsep pelaksanaan judicial review perda oleh mahkamah agung dilakukan melalui pembaharuan hukum acara persidangan judicial review di mahkamah agung dengan memasukan beberapa substansi penting, terkait sidang yang terbuka untuk umum, adanya proses pemeriksaan pendahuluan, pemeriksaan persidangan, pembuktian dan pengambilan putusan yang lebih terbuka dan fair.Kata Kunci : Peaturan Daerah, JudicialReview, dan Pembaharuan.